Integrated Strategic Decision-Making Framework for Freight Forwarding Industry Using AHP-Based Multi-Criteria Analysis: Evidence from Indonesia - Cholil Ubaidillah (PT. Samudra Solusi Profesional, 2026)
The freight forwarding industry faces increasing competitive pressure driven by globalization, technological advancement, and the expansion of international trade activities. Companies operating in this sector are therefore required to formulate competitive and sustainable business strategies to maintain operational performance and market competitiveness. This research proposes an integrated strategic formulation framework by combining the Multi-Criteria Decision Making–Analytical Hierarchy Process (MCDM-AHP) approach with Fred R. David’s strategic management model. The novelty of this research lies in integrating the Competitive Profile Matrix (CPM) into the input stage alongside the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices to strengthen competitive analysis and improve strategic decision-making accuracy. The research was conducted at an Indonesian freight forwarding company operating in inland, sea freight, and air freight services. Primary data were collected through interviews and stakeholder questionnaires, while secondary data were obtained from company documents and industry reports. The AHP method was employed to determine the relative importance of internal and external strategic factors, which were subsequently analyzed using the IFE, EFE, CPM, IE, SWOT, SPACE, BCG, Grand Strategy (GS), and Quantitative Strategic Planning Matrix (QSPM) frameworks. The findings demonstrate that the proposed framework improves strategic formulation by incorporating direct competitive positioning into the evaluation process. The results further indicate that digital logistics integration and specialized cargo service expansion represent the primary strategic priorities. This research provides a more objective and market-oriented framework for strategic decision-making in the freight forwarding industry.